Big Earth Data: a comprehensive analysis of visualization analytics issues - Patrick Merritt; Haixia Bi; Bradley Davis; Christopher Windmill; Yong Xue (Big Earth Data, 2018)
Big Earth Data analysis is a complex task requiring the integration of many skills and technologies. This paper provides a comprehensive review of the technology and terminology within the Big Earth Data problem space and presents examples of state-of-the-art projects in each major branch of Big Earth Data research. Current issues within Big Earth Data research are highlighted and potential future solutions identified.